The Impact Of Plant Growth Regulators (Pgrs) On Potato Plant Explant Somatic Embryogenesis And Embryonic Callus Induction - Lengkong, Edy F.; Pongoh, Jantje; Wanget, Sesilia A. (Jurnal Agroekoteknologi Terapan (JAT), 2026)
The purpose of this study was to develop methods for inducing potato somatic embryogenesis utilizing a variety of plant growth regulator types and concentrations, both directly and indirectly. Internodal explants of the Superjhon type of potato were used in the study, which was carried out from April to July 2024 at the Tissue Culture Laboratory, Faculty of Agriculture, Sam Ratulangi University. On MS media enriched with a mixture of NAA + kinetin and BAP + 2,4-D, embryogenic callus induction was performed. While indirect somatic embryogenesis was performed utilizing embryogenic callus on MS medium with different BAP concentrations, direct somatic embryogenesis induction was performed on MS media containing zeatin, IAA, and GA₃. The best embryogenic callus with a compact and granular texture was created by combining 1.5 mg/l BAP with 0.5 mg/l 2,4-D, according to the results. In MS medium + 1 mg/l zeatin + 0.02 mg/l IAA + 0.2 mg/l GA₃, direct somatic embryogenesis demonstrated the quickest and most efficient response, with the percentage of somatic embryo development reaching 54.5% in the fourth week. In the tenth week, indirect somatic embryogenesis yielded the greatest percentage of embryos (83%) in MS medium + 7 mg/l BAP. Compared to indirect ES, direct ES is quicker, easier, and results in more consistent shoot regeneration. Keywords: ZPT, tissue culture, somatic embryogenesis, potato ABSTRAK Tujuan penelitian untuk memperoleh teknik induksi embriogenesis somatik kentang melalui jalur langsung dan tidak langsung dengan penggunaan beberapa jenis dan konsentrasi zat pengatur tumbuh. Penelitian dilaksanakan di Laboratorium Kultur Jaringan Fakultas Pertanian Universitas Sam Ratulangi pada bulan April–Juli 2024 menggunakan eksplan internodus kentang varietas Superjhon. Induksi kalus embriogenik dilakukan pada media MS yang diperkaya kombinasi NAA + kinetin serta BAP + 2,4-D. Induksi embriogenesis somatik langsung dilakukan pada media MS yang mengandung zeatin, IAA, dan GA₃, sedangkan embriogenesis somatik tidak langsung dilakukan menggunakan kalus embriogenik pada media MS dengan berbagai konsentrasi BAP. Hasil penelitian menunjukkan bahwa kombinasi 1,5 mg/l BAP + 0,5 mg/l 2,4-D menghasilkan kalus embriogenik terbaik dengan tekstur kompak dan granular. Embriogenesis somatik langsung menunjukkan respons tercepat dan paling efektif pada media MS + 1 mg/l zeatin + 0,02 mg/l IAA + 0,2 mg/l GA₃ dengan persentase pembentukan embrio somatik mencapai 54,5% pada minggu keempat. Sementara itu, embriogenesis somatik tidak langsung menghasilkan persentase embrio tertinggi (83%) pada media MS + 7 mg/l BAP pada minggu ke-10. ES langsung lebih cepat, sederhana, dan menghasilkan regenerasi tunas yang lebih seragam dibandingkan ES tidak langsung. Kata kunci: kentang, kultur jaringan, embriogenesis somatik, ZPT